2021
DOI: 10.3390/app11199182
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Studying Bacterial–Fungal Interactions in the Microenvironments of Soil

Abstract: Due to their small size, microorganisms directly experience only a tiny portion of the environmental heterogeneity manifested in the soil. The microscale variations in soil properties constrain the distribution of fungi and bacteria, and the extent to which they can interact with each other, thereby directly influencing their behavior and ecological roles. Thus, to obtain a realistic understanding of bacterial–fungal interactions, the spatiotemporal complexity of their microenvironments must be accounted for. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 207 publications
(274 reference statements)
0
4
0
Order By: Relevance
“…However, growth behaviour is generally difficult to evaluate, therefore, it is often impossible to observe whether co-cultivation results in benefit or burden for either partner. The hyphal networks formed by the fungi might provide beneficial hitchhiking options 40 for P. helmanticensis and other bacteria, as they are usually immobile in the absence of a water layer 41 . Pseudomonas and also other bacteria such as Bacillus species , are known to stimulate mycelial growth or fruitbody formation: 1-octen-3-ol and ethylene consuming P. putida were found to stimulate the hyphal growth and fruitbody formation in Agaricus bisporus 42 .…”
Section: Discussionmentioning
confidence: 99%
“…However, growth behaviour is generally difficult to evaluate, therefore, it is often impossible to observe whether co-cultivation results in benefit or burden for either partner. The hyphal networks formed by the fungi might provide beneficial hitchhiking options 40 for P. helmanticensis and other bacteria, as they are usually immobile in the absence of a water layer 41 . Pseudomonas and also other bacteria such as Bacillus species , are known to stimulate mycelial growth or fruitbody formation: 1-octen-3-ol and ethylene consuming P. putida were found to stimulate the hyphal growth and fruitbody formation in Agaricus bisporus 42 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a simulation study reported that interaction patterns in predator–prey communities were relatively harder to predict compared to those in competitive communities ( Hirano and Takemoto, 2019 ). Therefore, we can supplement sequencing-based methods with experimental methods such as microfluidics, microscopy, and stable isotope probing ( Mandolini et al, 2021 ). Microfluidics will help emulate the natural plant microbiome environment but simplify it so that we can observe predator–prey behavior, and thus it will enable relatively high-throughput screening of predation.…”
Section: Ecological Interpretations Of Cross-kingdom Networkmentioning
confidence: 99%
“…To validate the mechanism behind the positive relationship between bacterial and fungal species in networks, pair-wise interaction can be examined again with the help of microcosm experiments, microfluidics, microscopy, and stable isotope probing ( Mandolini et al, 2021 ). With the microfluidic spatial design, fungal hyphae were observed to facilitate bacterial dispersal ( Mafla-Endara et al, 2021 ).…”
Section: Ecological Interpretations Of Cross-kingdom Networkmentioning
confidence: 99%
“…In light of the above, this special issue was introduced with the aim of opening a vivid discussion on the following topics: This special issue represents a concise and strong scientific reaction to our questions posed, with three Regular Full Length Research Articles ( [1] cited by 1, viewed by 474; [2] cited by 1, viewed by 878, and [3] cited by 28, viewed by 2772), and two Review Articles ( [4] viewed by 911; and [5] cited by 3, viewed by 1038). Various topics related to our posed questions-in general or in particular-have been addressed.…”
Section: 'Hide and Seek Of Soil Microbes-who Is Where With Whom And W...mentioning
confidence: 99%